The production of dissolved organic carbon by macroalgae and its consumption by marine bacteria: Implications for coastal ecosystems - Hall, Jack R.; Albert, Gerli; Twigg, Isla M.; Baltar, Federico; Hepburn, Christopher D.; Martin, Georg (Frontiers in Marine Science, 2022)
Through the fixation of large quantities of dissolved inorganic carbon (DIC), macroalgae facilitate the energetic foundation of highly productive coastal ecosystems. While the processes controlling photosynthesis and carbon fixation by macroalgae are well known, the fate of organic matter fixed by macroalgae is less well understood. This study quantified release rates of DOC by three ecologically significant Baltic macroalgae species: the perennial habitat forming Fucus vesiculosus and Furcellaria lumbricalis, and the seasonal fast-growing Ulva intestinalis, under both light and dark conditions. The released products were assessed using bacterial incubations whereby radiolabeled leucine was used to evaluate the uptake and lability of these products by marine heterotrophic bacteria. DOC was found to be released by both F. vesiculosus and U. intestinalis at rates of 0.27 mg C·h−1 under light and 0.13 mg C·h−1 per unit of dry mass under dark treatments, respectively, whereas F. lumbricalis DOC release was observed to be negligible under both light and dark. Our findings further validate previous hypotheses that factors such as photosynthetic activity are a primary driver behind DOC release and that DOC release is not an entirely passive process. Additionally, we reaffirm the need to relate a given species life characteristics and habitat in order to understand why DOC products are released. The consumption of macroalgae-derived DOC by heterotrophic bacteria reveals that released DOC is variable in its lability. After a period of 12 h and under maximum photosynthetic conditions, the release of DOC by F. vesiculosus and U. intestinalis achieved a peak rate of 219 µg C·L−1·day−1 and 214 µg C·L−1·day−1 for each gram of dry weight material, respectively, directly into the microbial loop via heterotrophic bacterial consumption. In contrast, F. lumbricalis’ low rate of DOC release and the subsequent low bacterial consumption indicate that habitats dominated by this species have a reduced importance in the transfer energy via the microbial loop. These findings have implications for how we view carbon transfer within coastal food webs and highlight how changes in species composition and coverage may dramatically affect coastal ecosystem productivity through the microbial loop.